Derivatives and the financialisation of the Italian state. Issue 2 (3rd March 2016) - Lagna, Andrea
ABSTRACT: The existing literature on financialisation has devoted insufficient attention to how governments wield the market-based practices and technologies of financial innovation to pursue statecraft objectives. Because of this inattention, scholars have missed the opportunity to examine a crucial facet of the financialisation of the state . To remedy this limitation, the present article investigates how and why the Italian government designed derivatives-based strategies during the 1993–9 period. It argues that these tactics gained momentum in the context of the political struggles that developed in Italy beginning in the late 1980s. In particular, the study shows how a neoliberal-reformist alliance came to power and used financial innovation to comply with the Economic and Monetary Union (EMU) admission criteria. EMU dynamics enhanced the power position of the neoliberal-reformist coalition vis-à-vis the country's traditional political and business establishment. This work offers insights that go beyond the specificities of the Italian case. It encourages further research on how governments in other countries simultaneously exposed state institutions to financial speculation and gained access to a range of new instruments through which they could manage state affairs in a financialised manner.